Dynamic instability of a sol-gel-derived thin film - Kwon, S. Joon; Park, Jae-Gwan (AMER CHEMICAL SOC, 2008)
We present a study on the dynamic instability of a sol-gel-derived (SG) thin film on a nonwettable substrate. Because of the structural instability accompanied by syneresis stress in a film deposited on the substrate, there exists a regular distribution of dewetting patterns required to relieve the in-plane stress, such as holes in the earlier stages, and droplets accompanying a regular polygonal distribution in the later stages of the dynamic instability. The characteristic length scales in each stage scaled linearly with the film thickness during the duration of dewetting. For the formation of holes during the earlier stages of rupture of the film, the dewetting velocity was analyzed with a viscous sintering theory of a SG thin film. In the earlier stages of the dynamic instability, the dewetting velocity decreases with increasing dewetting time and increases with increasing the initial film thickness, which indicates that the SG thin film behaves partially like a slipping polymer thin film. In the final times of the film rupture, the radius of the hole has a linear relationship with the film thickness, and the growth rate of the hole (dewetting velocity) is nearly constant, regardless of the film thickness. These dewetting behaviors indicate that the SG thin film in the final times of the rupture is somewhat similar to nonslipping film. From these observations, we found that the dewetting behavior of a SG thin film has ambivalent dewetting characteristics of slipping and nonslipping films and that a SG thin film is not a purely viscous film.
Keywords: POLYMER; SURFACES; ZNO